FEDERAL UNITS AND INTERNATIONAL LOANS - Ahmed Bahram Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The participation of Federal Union in international Loan is associated with the suspension of the Federal Government Constitution. There is no real federalism if the international relations are exclusively by the central government. Federalism have some characterize one of them is fiscal independent to manage himself by different way such as impose duties on goods for both export and import, International borrowing is a modern mechanism which is the regions can resort to when they need it. In the case of Quebec National Assembly in 2002 unanimously adoption of the law that requires the National Assembly’s approval of all international agreements assent by Canada and that involve Quebec’s matters of competence, Unlike the KRG.Although the Canadian Federalism known's as more centralized in decision-making process. Fiscal decentralization has another adventures to decline risk of macroeconomic instability. So free trade between countries and globalization are among factors that have encouraged many regions and territories to insist their quest for an international competence, could they can rely on selfgovernance and reduce the financial burden on the central government. From this point I concentrate on prominent role of the regions in how to obtain international borrowing on perspective of international Law. And take the right of the federal territories until if there an obstruction by the federal Government when the aim is developing the regions and revive of his economy. in the case of KRG have right to join an international Loan and transgovernmental fiscal relations in order to promote the region’s Economy, health care and social amenities, it becomes a defacto which is acceptable of the international community. KRG can benefit from the experience of the Québec in the event of their independence from Iraq on how to share the Iraqi debts between them. this study reveals that the debt sharing formulars; the Per capita estimates, GDP estimates, Belanger-Campeau and the historical benefits have good prospect for and applicable to the situation of KRG. Since the GDP estimates type is derived from the relative value of the KRG GDP against that of Iraq as a whole, this type could be appropriate for KRG considering its vast GDP contribution to the national coffer.